2020
DOI: 10.1002/qua.26267
|View full text |Cite
|
Sign up to set email alerts
|

Large thermoelectric figure of merit in hexagonal phase of 2D selenium and tellurium

Abstract: We found a large thermoelectric figure of merit in the hexagonal phase of 2D selenium and tellurium from first‐principles calculations. The hexagonal phase (α) is obtained from three atomic layers truncated along the [001] direction of trigonal Te and Se bulk in the equilibrium structure. We found the α‐Se structure dynamically stable. The calculated electronic structures of α‐Se and α‐Te show interesting semiconductor character for both electronic and optoelectronic applications. Furthermore, the obtained ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…[246][247][248] In the following, the thickness direction is defined as the z-direction, and the chain direction is defined as the y-direction for the chain-like and tetragonal phases, whereas for the rhombic phase the y-direction extends along the armchair direction, due to the loss of the original chain structure by reconstruction. 247 The space group, cohesive energy, lattice constants, bond length, corrugation, and layer thickness of the trigonal, 246,[248][249][250] tetragonal, 246,251,252 rhombic, 245,248,[252][253][254] and monoclinic 224,249 structures of selenene are presented in Table 12, along with the bonding information and structural properties of the trigonal, 247,250,255,256 tetragonal, 247,255 rhombic, [252][253][254][255] and monoclinic 249 structures of tellurene. This data makes possible a discussion of bonding-structure-performance relationships for these recently discovered 2D materials with novel structures deviating from previous hexagonal 2D materials.…”
Section: Group Iv-vi Monolayersmentioning
confidence: 99%
See 1 more Smart Citation
“…[246][247][248] In the following, the thickness direction is defined as the z-direction, and the chain direction is defined as the y-direction for the chain-like and tetragonal phases, whereas for the rhombic phase the y-direction extends along the armchair direction, due to the loss of the original chain structure by reconstruction. 247 The space group, cohesive energy, lattice constants, bond length, corrugation, and layer thickness of the trigonal, 246,[248][249][250] tetragonal, 246,251,252 rhombic, 245,248,[252][253][254] and monoclinic 224,249 structures of selenene are presented in Table 12, along with the bonding information and structural properties of the trigonal, 247,250,255,256 tetragonal, 247,255 rhombic, [252][253][254][255] and monoclinic 249 structures of tellurene. This data makes possible a discussion of bonding-structure-performance relationships for these recently discovered 2D materials with novel structures deviating from previous hexagonal 2D materials.…”
Section: Group Iv-vi Monolayersmentioning
confidence: 99%
“…Moreover, helix-to-layer transformations from 1D trigonal to 2D tetragonal phases can be induced by mechanical strain. 247 The currently available mechanical properties, which are limited to tetragonal 251 and rhombic [252][253][254] selenene as well as trigonal, 247 tetragonal, 258,259 and rhombic 252,258 tellurene, are shown in Table 13. The dependence of the Young's moduli and ultimate strengths on the bond lengths of the tetragonal and rhombic structures of selenene and tellurene is presented in Fig.…”
Section: Group Iv-vi Monolayersmentioning
confidence: 99%
“…Wu et al 44 constructed a 2D FET device with large drain current of 300 mA mm −1 , high mobility and high on/off ratio. Te has superior transport properties that make it suitable for thermoelectric applications 41,43,45,46 . It has high carrier mobilities leading to good electrical conductivity and the heavy Te atoms result in flat bands towards conduction region that increase the Seebeck coefficient 47 .…”
Section: Introductionmentioning
confidence: 99%
“…By comparison, the k l of SeTe 2 monolayers is much lower than that of Se 2 Te monolayers, as shown in Figure 7 , which is benefited from the large weight of the constituent elements [ 10 ] and weak bonding [ 51 , 52 ] (see Figure 4 ). Notably, it can be seen from Figure 7 that both the k l of Se 2 Te and SeTe 2 decrease with the biaxial tensile strain.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Zhu et al [ 4 ] and Chen et al [ 5 ] predicted and successfully synthesized the tellurene on highly oriented pyrolytic graphite (HOPG) substrates by using molecular beam epitaxy. Subsequently, a new two-dimensional (2D) materials family, the group-VI elemental 2D materials, has attracted significant attention due to its high carrier mobility, high photoconductivity, and thermoelectric responses [ 6 , 7 , 8 , 9 , 10 , 11 ]. Recent studies confirmed that the compounds composed of Te and Se have excellent thermoelectric and electronic transport properties [ 7 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%